Sea snail: An alternative source for nano-bioceramic production - (:unkn) unknown (Trans Tech Publications Ltd, 2012)
The production of nano-calcium phosphate, such as HA (hydroxyapatite), materials from synthetic chemicals could sometimes lead to a costly and tedious work. Sea creatures could be an alternative way to produce very fine and even nano-structured calcium phosphate materials. Nacres vastly consist of rich calcium carbonate and/or aragonite mater. With simple conversion methods, like hotplate stirring, various bioceramic structures could be produced suitable for thin film coatings with various methods, like pulsed laser deposition (MAPLE). This study is part of a bigger project which eventually and ultimately aims to produce nano-phases of calcium phosphate biocompatible bioceramics, which can be used for biomedical coatings. In this particular study, we focus at transforming chemically, using hotplate stirring method, local sea snail shells rapana thomasiana. Cleaned sea snail samples were provided from local markets in Istanbul. The shells were smashed down, ball-milled and the powder was sieved (<100 μm powder particles). Differential thermal analysis (DTA/TG) was employed to evaluate the exact CaCO3 content of the shells. According to these results, the required volume of H3PO4 was added in order to set the molar ratio of Ca/P (during hotplate stirring) either 10/6 or 3/2 (these ratios correspond to HA and TCP, respectively). SEM and X-ray diffraction analyses were conducted. The SEM observations showed brick-like particles were formed with sizes <5 μm. From the X-ray diffraction analysis, predominantly monetite, which can be considered as a precursor of HA and TCP, was detected. The results of this study showed that to produce HA and other bioceramic phases, hot-plate stirring method is a reliable, fast, rapid and economic method when compared to other tedious HA production methods. Moreover, sea snail shells are very good candidate materials to produce fine powders with hotplate stirring method for various tissue engineering applications. © (2012) Trans Tech Publications.
Keywords: Hotplate; Monetite; Natural nano-bioceramics; Sea snail